Is the High-Intensity Focused Electromagnetic Energy an Effective Treatment for Urinary Incontinence in Women? - Tosun H; Akınsal EC; Sönmez G; Baydilli N; Demirci D (Therapeutics and Clinical Risk Management)
Halil Tosun, Emre Can Akınsal, Gökhan Sönmez, Numan Baydilli, Deniz Demirci Department of Urology, Erciyes University Medıcal Faculty, Kayseri, TürkiyeCorrespondence: Emre Can Akınsal, Department of Urology, Erciyes University Medical Faculty, Kayseri, Türkiye, Tel +90 532 588 16 46, Fax + 90 352 437 52 85, Email emreakinsal@hotmail.comPurpose: To assess the effectiveness and safety of high-intensity focused electromagnetic technology (HIFEM) used as a therapeutic approach in patients with stress and mixed urinary incontinence.Patients and Methods: Thirty-five females suffering from stress and mixed urinary incontinence were included in the study. The electromagnetic chair (BTL EMSELLA®) was applied to the patient’s pelvic area twice a week for 28 minutes, totaling 6 sessions. The patients’ “International Consultation on Incontinence Questionnaire‐Short Form” (ICIQ-SF) scores and the number of daily absorbent pad usage were recorded. Results were evaluated after the sixth session and at a first-month follow-up.Results: The average ICIQ‐SF score at baseline was 10.18 ± 4.19 (ranging from 2– 18) which declined to 5.33 ± 3.97 after six sessions, and further improved to 4.26 ± 3.94 points at the one‐month follow‐up. After six sessions, an average improvement of 52.06% in ICIQ-SF score was observed, and after one month of follow-up, an average improvement of 59.6% was detected, which was found to be statistically significant (p=0.038). In addition, the mean number of pads used per day decreased to 1.25 ± 1.54 after treatment, a significant improvement was observed, and the mean daily pad use decreased further to 0.91 ± 1.11 at the first-month follow-up.Conclusion: HIFEM has demonstrated in our study its ability to safely and effectively treat female patients suffering from stress and mixed urinary incontinence, as evidenced by significant improvements in symptoms and quality of life observed in clinical trials.Keywords: urinary incontinence, pelvic floor muscle, HIFEM